High throughput computations of the effective removal of liquified gases by novel perchlorate hybrid material - Tomsmith O. Unimuke; Hitler Louis; Onyinye J. Ikenyirimba; Gideon E. Mathias; Adedapo S. Adeyinka; Chérif Ben Nasr (Scientific Reports, 2023)
Abstract The utilization of hybrid materials in separation technology, sorbents, direct air capture (DAC) technology, sensors, adsorbents, and chiral material recognition has increased in the past decade due to the recognized impact of atmospheric pollutants and hazardous industrial gases on climate change. A novel hybrid material, perchlorate hybrid (PClH), has been proposed in this study for the effective sensory detection and trapping of atmospheric pollutants and industrial hazardous gases. The study evaluated the structural properties, adsorption mechanism, electronic sensitivity, and topological analysis of PClH using highly accurate computational methods (M062X-D3BJ/def2-ccpVTZ and DSDPBEP86/def2-ccpVTZ). The computational analysis demonstrated that PClH has considerable adsorption energies and favorable interaction with CO2, NO2, SO2, COCl2, and H2S. PClH is more suitable for detecting liquefiable gases such as COCl2, CO2, and SO2, and can be easily recovered under ambient conditions. Developing such materials can contribute to reducing hazardous gases and pollutants in the atmosphere, leading to a cleaner and safer environment.